Edukasi dengan Media Booklet terhadap Peningkatan Pengetahuan, Sikap dan Praktik Ibu Hamil dalam Pencegahan Berat Badan Lahir Rendah - Christin Desi Anggreyenti; Apoina Kartini; Martini Martini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effect of education using booklet media on preventing low birth weight on increasing knowledge, attitudes, and practices of pregnant women in preventing low birth weight in the work area of the Batubi Health Center, Natuna Regency. The method used is a quasy experiment with a non-randomized pre-post-test control group design. The results showed that the statistical test obtained a p-value of 0.000. In conclusion, there is an increase in the knowledge, attitudes, and practices of pregnant women towards preventing low birth weight after being given education using booklet media. Keywords: Low Birth Weight, Booklet, Pregnant Women